Extracellular Vesicles From High Glucose-Treated Podocytes Induce Apoptosis of Proximal Tubular Epithelial Cells - Huang, Ying; Li, Ruizhao; Zhang, Li; Chen, Yuanhan; Dong, Wei; Zhao, Xingchen; Yang, Huan; Zhang, Shu; Xie, Zhiyong; Ye, Zhiming; Wang, Weidong; Li, Chunling; et al. (Frontiers in Physiology, 2020)
Diabetic kidney disease (DKD) is a serious and common complication of diabetes. Extracellular vesicles (EVs) have emerged as crucial vectors in cell-to-cell communication during the development of DKD. EVs may mediate intercellular communication between podocytes and proximal tubules. In this study, EVs were isolated from podocyte culture supernatants under high glucose (HG), normal glucose (NG), and iso-osmolality conditions, and then co-cultured with proximal tubular epithelial cells (PTECs). miRNA sequencing was conducted to identify differentially expressed miRNAs of podocyte EVs and bioinformatics analysis was performed to explore their potential functions. The results showed that EVs secreted from HG-treated podocytes induced apoptosis of PTECs. Moreover, five differentially expressed miRNAs in response to HG condition were identified. Functional enrichment analysis revealed that these five miRNAs are likely involved in biological processes and pathways related to the pathogenesis of DKD. Overall, these findings demonstrate the pro-apoptotic effects of EVs from HG-treated podocytes on PTECs and provide new insights into the pathologic mechanisms underlying DKD.